ANALYSIS OF ADDED VALUE AND MARKETING EFFICIENCY OF BROWN SUGAR PRODUCTS IN MALANGGA SMALL AND MEDIUM ENTERPRISES, GALANG DISTRICT, TOLITOLI REGENCY: ANALISIS NILAI TAMBAH DAN EFISIENSI PEMASARAN PRODUK GULA MERAH DI USAHA KECIL DAN MENENGAH MALANGGA, KECAMATAN GALANG, KABUPATEN TOLITOLI - Ardiyanti, Ardiyanti (STIE MUJAHIDIN TOLITOLI, 2024)
This study aims to: 1) To find out the added value produced by farmers in brown sugar processing products in Malangga Village, Galang District, Tolitoli Regency, 2) To find out the level of marketing efficiency related to marketing margin, farmer's share and the ratio of profits and costs of brown sugar processing products in Malangga Village, Galang District, Tolitoli Regency. This study uses a qualitative research type to explain the variables studied by involving 11 key informants who are directly involved from the brown sugar processing process to its distribution to consumers which are taken by purposive sampling techniques. The results of the study show that: 1) Processing sap water into brown sugar causes added value to the palm commodity. Added value can be in the form of added value to the product, where raw materials that were originally raw materials from the processing process can be used so that they have more economic value; 2) The four marketing channels of brown sugar are classified as very efficient, each marketing channel gets a greater profit than the cost.